(untitled) (Victoria Journal of Management, 2025)
The rapid evolution of technological advancements and shifting consumer behavior necessitates a comprehensive understanding of emerging trends and research directions in digital marketing and customer engagement. This study presents a comprehensive bibliometric analysis of 6,220 publications from SCOPUS and Web of Science (2010–2024) to map the conceptual structure and thematic evolution of digital marketing and customer engagement research. Utilizing tools such as Biblioshiny, the analysis identifies key trends through keyword co-occurrence, thematic mapping, and correspondence analysis. The findings reveal a dynamic shift from foundational consumer preferences and advertising themes to emerging domains such as influencer marketing, sustainability, and AI-driven strategies. Thematic clusters underscore the rising influence of social media, electric vehicles, and sentiment analysis in shaping consumer behavior, while motor themes like willingness to pay and choice experiments remain crucial. Niche areas such as game theory and e-commerce platforms highlight the underexplored research opportunities. This study emphasizes the transformative role of artificial intelligence in customer experiences and the necessity of interdisciplinary collaboration to address evolving market challenges. Despite limitations, including language biases and database constraints, this research offers actionable insights for academia and practice. This study advocates for future exploration of sustainability, global consumer trends, and advanced analytics, enabling businesses to craft adaptive strategies in a digitally competitive landscape. This analysis provides a roadmap for advancing theoretical frameworks and fostering deeper customer connections and sustainable brand growth.